2020
DOI: 10.1039/d0sc02097d
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing semipermeability of the cell membrane using a pH-responsive ratiometric AIEgen

Abstract: By utilizing a pH-responsive ratiometric AIEgen, dihydro berberine (dhBBR), ion trapping phenomenon was successfully visualized.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The compound 52 showed fluorescence enhancement under viscous conditions and crystal states and exhibited dramatic emission wavelength changes from 454 to F I G U R E 9 Chemical structures of different heterocyclic AIEgens and effect of different substituents as rotors and recognition sites for their prospective use for bioapplications 511 nm in the pH range of 7-10. [86] Considering the conformational similarity of 52 to 51, the AIE performance was also caused by the RIV. The ion trapping phenomenon was visualized in live cells using the pH-dependent ratiometric fluorescence changes of 52.…”
Section: Heterocycles As Aiegensmentioning
confidence: 99%
“…The compound 52 showed fluorescence enhancement under viscous conditions and crystal states and exhibited dramatic emission wavelength changes from 454 to F I G U R E 9 Chemical structures of different heterocyclic AIEgens and effect of different substituents as rotors and recognition sites for their prospective use for bioapplications 511 nm in the pH range of 7-10. [86] Considering the conformational similarity of 52 to 51, the AIE performance was also caused by the RIV. The ion trapping phenomenon was visualized in live cells using the pH-dependent ratiometric fluorescence changes of 52.…”
Section: Heterocycles As Aiegensmentioning
confidence: 99%
“…• Gu et al . [ 44 ] developed a fluorescent probe based on dihydroberberine that showed that ionized berberine had a substantially lower cell penetration than the non-ionized form.…”
Section: Relationship Between Deregulated Ph and Mdrmentioning
confidence: 99%
“…Moreover, in recent years, some sustainable natural materials have attracted more and more attention. These materials have been widely applied in the field of biomedicine; however, their fluorescence characteristics have got little attention . In this work, an AIE polysaccharide with the CTE mechanism which comes from natural resources, oat-β-Glu, is found.…”
Section: Introductionmentioning
confidence: 99%